Case report: Widely split P' waves in a patient with focal atrial tachycardia - Jiang, Hao; Ruan, Zhongbao; Ren, Yin; Ding, Xiangwei (Frontiers in Cardiovascular Medicine, 2024)
Background: Widely split P waves in sinus rhythm have been reported previously. Widely split P' waves in focal atrial tachycardia (AT) on a surface electrocardiogram (ECG) have rarely been reported. The electrophysiological mechanism is relatively difficult to clarify, requiring electrophysiological study. Case Summary: A 67-year-old patient, who had undergone two radiofrequency ablations for atrial fibrillation, presented with recurrent palpitation. During the palpitation episode, the 12-lead ECG showed AT with a 3:1 atrioventricular conduction rate. P' waves were markedly prolonged in duration and widely split in morphology. Electrophysiological study showed that the tachycardia arose from the left atrial appendage (LAA) and was conducted through two distinct pathways. The impulse of one pathway was transmitted solely via the superior part of the atrium, including the Bachmann bundle. The second pathway was conducted via the coronary sinus and transmitted the impulse from the LAA to the ventricle. After the site showing the earliest activation was ablated, repeated intravenous infusion of isoprenaline and programmed atrial stimulation did not induce tachycardia. Conclusion: Widely split P' waves in AT indicate intra- and inter-atrial conduction block and can easily be overlooked due to low voltage areas. Electrophysiological study is crucial for identifying the origin of the tachycardia and elucidating the mechanistic details.